Time-frequency methods based on the Wavelet transform - Serrano, Eduardo P. (2012)
The information contained in an analog signal is reveled by its numerical representation. The Fourier pair, in two complementary representations, expounds time and frequency structures. However, to detect and characterize those events which combine both structures in diverse and complex patterns, it is necessary to implement more refined methods joint with appropriate time-frequency representations. Among various options, the wavelet transform provides an efficient tool time-scale. Their extensions lead to appropriate representations coexisting in the same analytical context. Make it possible implement flexible strategies, well adapted to the characteristics of the signal.